GENDER INEQUALITY OF MAGGIE'S LIFE IN GEORGE ELIOT'S THE MILL ON THE FLOSS: A FEMINIST APPROACH - NURMALIA P. , DEWI (2007)
This research paper is primarily intended to identify how the major character struggles for get equality with man in George Eliot's The Mill on the Floss viewed from Feminist approach and to analyze the novel based on its structural elements. In analyzing The Mill on the Floss, the writer uses descriptive library method and feminist approach. The data sources are primary and secondary data sources. The method of the data of the data collection is literary research. The technique of data analysis is descriptive analysis. The outcome of the study shows the following conclusions. First, the story reflects the rural life during the 19th in the town of St. Ogg's near the river Floss. Second, it describes Maggie's struggle to get equality for her brother. Maggie and Tom Tulliver endure childhood and young adulthood while experiencing the harsh realities of poverty, devotion and love. At last it is known that Maggie who is a representation of women in Victorian Age has struggled to win the approval of his brother. She also refuses to obey her brother and lives independently. She earns money by working as a teacher. And her effort to be independent and not being dependent with her brother is categorized as feminism attitude.